2020
DOI: 10.9734/ejnfs/2020/v12i830256
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Pan Bread Made with Wheat Flour and Psyllium Seeds for Obese Patients

Abstract: In this covenant of functional foods, the world seeks for new healthier food products with appropriate proportions of bioactive constituents such as fiber, mineral elements, amino acids and phenols. The psyllium seed has good nutritional and pharmaceutical properties; therefore, its incorporation in pan bread could be beneficial in improving human health. In the current study, partial substitution of wheat flour (WF) with psyllium seed flour (PSF) at levels of 5%, 10% and 15% were carried out to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
4
2
0
Order By: Relevance
“…CSP has higher content of crude protein, crude fat, crude fibre and ash and lower content of total carbohydrates than that of wheat flour 72% extraction. These values agreed with those reported by [20] Stated that the crude protein, crude fat, ash, crude fibre and total carbohydrates of wheat flour 72% extraction were 11.81, 0.75, 0.45, 0.84 and 86.98%, respectively [28]. studied that CSP contain 36.57% lipid, 26.1% protein, 22.22% crude fibre 9.96% nitrogen-free extract and 5.15% ash.…”
Section: Chemical Composition Of Wheat and Chia Floursupporting
confidence: 90%
See 1 more Smart Citation
“…CSP has higher content of crude protein, crude fat, crude fibre and ash and lower content of total carbohydrates than that of wheat flour 72% extraction. These values agreed with those reported by [20] Stated that the crude protein, crude fat, ash, crude fibre and total carbohydrates of wheat flour 72% extraction were 11.81, 0.75, 0.45, 0.84 and 86.98%, respectively [28]. studied that CSP contain 36.57% lipid, 26.1% protein, 22.22% crude fibre 9.96% nitrogen-free extract and 5.15% ash.…”
Section: Chemical Composition Of Wheat and Chia Floursupporting
confidence: 90%
“…In pan bread preparation, the straight dough method was made according to the method defined by El-Hadidy [20]. The control of pan bread was (300 g of WF and other materials), also four recipes 1, 2, 3 and 4 comprise (291 g WF+ 9 g CSP), (282 g WF+ 18 CSP) (273g WF +27g CSP) and (264 g WF +36 g PSP), respectively.…”
Section: Pan Bread Processingmentioning
confidence: 99%
“…Blend (5) recorded the highest value of protein 11.414% compared to blends (1, 2, 3 and 4) were 6.436%, 10.058%, 10.410% and 10.964%, respectively (on dry basis).Table 3 show that, blend (5) have the highest value of crude fiber and crude ether extract followed by blend (4), blend (3), blend (2) and blend (1) which contained (5.633% and 10.220%), (5.070% and 10.370%), (4.506% and 10.505%), (4.013% and 10.668%) and (0.290% and 8.686%), respectively (on dry basis).On the other hand, Blend (5) the lowest values of total carbohydrates , energy 70.829% and 430.202 kcal/100ց respectively, compared to blends 1, 2, 3, and 4 were (83.874%, 73.077%, 72.485% and 71.659%) and (44.316, 437,936, 435,876 and 433.124 kcal/100ց samples), respectively. These results agree with earlier work of (Elhadidy et al, 2020) that showed addition of quinoa flour to rice flour increase crude protein in bakery products.…”
Section: Proximate Chemical Composition Of Crackers (On Dry Weight)supporting
confidence: 93%
“…Although processed wheat flour is the primary component in bread goods, its protein content is a lower quantity than that of other cereals, Gómez et al,(2010) reported that wheat flours used in baking have a lower protein level. These findings were confirmed by the reported work of ( Gokavi et al, 2004;Toliba and Mohamed, 2019;El-Hadidy, 2020), where garden cress seeds powder is a rich source of dietary fiber, carbohydrates, protein, fat, ash, calcium, potassium, phosphorus, magnesium, iron, zinc, polyphenols and flavonoids. Cake industry challenges include increased storage, quality control, and cost reduction (Cauvain and Young, 2006).…”
Section: Discussionsupporting
confidence: 83%